Assessment Task-Based Language Needs of Sport Management Students (Case study: University of Mazandaran) - Morteza Dousti; Goudarz Alibakhshi (Allameh Tabataba'i University Press, 2019)
Purpose: The purpose of this research was to identify specialized language needs of MA students in University of Mazandaran. Method: This study was mix method instruments which would deeply explore the perspectives of English for specific purpose teachers and students about task-based language needs of teaching ESP. Semi-structured interview was carried out with a number of teachers and students in the field of sport management. The statistical population of the stage includes some teachers and students in the field of sport management. The sampling method was Purposive sampling and Sampling continue until theoretical saturation. Three ESP teachers who have been teaching ESP to the students for at least four years participated in this study. They were all selected through purposive sampling. Also, MA and Ph.D. (twelve persons) students who had passed this course were selected in qualitative stage. In quantitative stage and based on the results of the first stage, the questionnaire was designed. This questionnaire was broadly distributed amongst students and teachers (33 persons) in the field of sport management. Descriptive and Inferential statistics, were used to analyze the demographic information of the participants and their responses. Results: The results of the study showed that the main real tasks which were most frequently used in the English sport management classes include Participating in daily conversations, giving lectures at conferences, Conversation with foreign experts, Understanding daily conversations. The method of working with and using English to English dictionary to take advantage of all the capabilities contained in it. Conclusions: The information obtained about the target tasks and their frequency can be employed when taking decisions about which tasks should be part of a curriculum.